Estudo sobre a evasão escolar nos últimos dez anos: uma discussão bibliográfica - Garcia, Ana Flávia Iasseck (2021)
Student dropout is a phenomenon present throughout the educational field and has become an increasingly frequent object of study especially in the university context. In order to develop strategies to reduce dropout rates, it is extremely necessary to acquire more knowledge on the subject. Thus, this paper aims to present a literature review on dropouts in the last ten years with emphasis on higher education. It has as reference for the study national journals in the area of Education classified as Qualis A1, A2, B1 and B2, thus providing an overview of what has been researched on this theme. After the search, were found 446 articles, but only 84 were selected for analysis, since they were the ones that dealt with dropout in a more indepth way. The analysis of the articles found was perform by means of the "Content Analysis" of Bardin (2004) and grouped into nine categories, after the individual analysis of the papers, it was verify that dropout is a complex phenomenon and difficult to categorize since there are several causes that lead students to abandon their studies. This confirms the need to investigate this topic in a more intense and specific way, so that more efficient measures and public policies can be developed.